Determinants of smallholder farmers access to formal credit: the case of Metema Woreda, North Gondar, Ethiopia - Yehuala, S. (Haramaya University, 2008)
In Ethiopia, among other things, lack of finance is one of the fundamental problems hampering production, productivity and income of rural farm households. Since access to institutional finance is very limited, the majority of the poor are forced to search financial services through informal channels. The study was sought to ascertain factors that affect smallholder farmer’s access to formal credit and also the status of women and different wealth groups’ access to formal and informal credit sources in the study area. A two stage sampling method was employed to select three out of eighteen rural peasant associations and 130 farm households. Structured interview schedule was developed, pre-tested and used for collecting quantitative data for the study from the sampled farm households. Focus group discussion, group interview and field observations were held to generate qualitative data. Descriptive statistics and logit model were used for analyzing quantitative data. The output from the study indicates that 56 (43.1%) of the sampled farm households were formal credit users, whereas the remaining 74 (56.9%) were non-users. It was also found out that credit access to female headed households is still limited and the difference between the wealth groups in accessing credit from the formal sources was also statistically significant. Farmers acknowledge group lending that solves the problem of collateral requirement by lending institutions, controls misuse of borrowed funds and minimizes the risk of default and they also recognize the provision of saving services by MFI, while strongly criticizing the isolation of very poor farmers from the group formation. Moreover, the smaller loan size, earlier saving requirement which was not convenient to the farmers, and repayment period by the MFI were among the critical problems. Participation in extension package programs, Experience in credit use from the formal sources, total cultivated land size, number of livestock in TLU, collateral or group formation and membership of FMSC were highly important in influencing access to formal credit use as evidenced by the model output. Therefore, policy aimed to accelerate agricultural development in the area could be successful if these factors and problems are taken into consideration to access credit from the formal financial sources.